SATISFACTION WITH TRAVEL SCALE (STS) BEFORE AND AFTER IMPLEMENTING NEW IMPROVEMENT (STUDY CASE: KARLSTADSBUSS SWEDEN) - Sukmayasa, I Made; Irawan, Muh. Zuhdy; Friman, Margareta (Prosiding Forum Studi Transportasi Antar Perguruan Tinggi, 2015)
Multiple regression analysis are used to examine the dimensions of satisfaction with travel scale (STS). Such method is used to understand the behavior changing before and after implementing of quality improvement since the karstadsbuss presented the new comfortable bus. The random sample data based on subjective response were collected before and after implementation of new quality attributes in Karlstad city (n = 459).   The data before and after contains of different group of respondents.  The process is statistically, the high loadings factors are expected to explain of dimensions of STS (i.e. positive activation, positive deactivation, and cognitive evaluation). The result yielded that the average of items were significantly increase in almost all items. The result also revealed that accessibility and mobility factor was the greatest effect for positive activation and cognitive evaluation and in the meanwhile, information on board affect positive deactivation.